Analytical Concordance of Diverse Point-of-Care and Central Laboratory Troponin I Assays. (23rd October 2019) - Tsui, Albert K Y; Lyon, Martha E; van Diepen, Sean; Goudreau, Bobbi Lynn; Thomas, Dylan; Higgins, Trefor; Raizman, Joshua E; Füzéry, Anna K; Rodriguez-Capote, Karina; Estey, Mathew; Cembrowski, George
Abstract: Background: Cardiac troponin I (cTnI) 99th percentile cutoffs, used in the diagnosis of acute myocardial infarction, are not standardized across cTnI assays. We compared 3 point-of-care (POC) and 1 central laboratory contemporary cTnI assays against the Abbott high-sensitivity (hs) cTnI to evaluate the analytical concordance and the feasibility of using a single cutoff value for all assays. Methods: Fresh blood samples collected from 102 inpatients in the coronary care unit were measured on central laboratory instruments (Beckman Coulter DxI AccuTnI+3 TnI, Abbott Architect hs-TnI) and cTnI POC analyzers (Alere Triage Troponin I, Radiometer AQT90, Abbott i-STAT). Agreement and correlation between the contemporary cTnI assays and hs-cTnI assay were assessed using regression analysis. Proportional bias was assessed using Bland–Altman plots. Concordance between the contemporary cTnI and hs-cTnI assays was determined by diagnostic contingency tables at specific cutoffs. Results: Most POC cTnI assays had excellent correlation with the Abbott hs-cTnI method ( r 2 = 0.955–0.970) except for Alere Triage ( r 2 = 0.617), while proportional bias is evident between all cTnI assays. Overall concordance between POC contemporary cTnI assays and hs-cTnI assay was 80% to 90% at their respective 99th percentile cutoffs. The concordance increased to 90% to 95% when a fixed cutoff of 0.03 to 0.05 ng/mL was used across the assays. Conclusions: This study demonstrates poor analytical concordance between cTnI assays at the 99th percentile and supports the notion of a single clinical decision limit for cTnI and consequently standardization of diagnostic protocols despite the analytical differences among these assays.